2017
DOI: 10.3233/blc-170119
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Transurethral Resection of Bladder Tumors – Current Practice and Future Outlooks

Abstract: Transurethral resection of bladder tumor (TURBT) under white light cystoscopy (WLC) is the cornerstone for the diagnosis, removal and local staging of non-muscle invasive bladder cancer (NMIBC). Despite technological improvements over the decades, significant shortcomings remain with WLC for tumor detection, thereby impacting the surgical quality and contributing to tumor recurrence and progression. Enhanced cystoscopy modalities such as blue light cystoscopy (BLC) and narrow band imaging (NBI) aid resections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 75 publications
(58 reference statements)
0
25
0
Order By: Relevance
“…Even though we performed multivariable analyses to account for the effects of standard clinicopathological variables, several other factors could have influenced the results. For instance, during the study period, there have been significant advances in optical imaging technologies and resection techniques with the goal of facilitating the surgeon to better identify bladder lesions and improve the quality of TURBT, and this could have influenced our present findings .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though we performed multivariable analyses to account for the effects of standard clinicopathological variables, several other factors could have influenced the results. For instance, during the study period, there have been significant advances in optical imaging technologies and resection techniques with the goal of facilitating the surgeon to better identify bladder lesions and improve the quality of TURBT, and this could have influenced our present findings .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported residual tumour at re‐TURBT in 30% of patients at the prior resection site and 70% with tumour elsewhere in the bladder . Tumour persistence and early recurrence may be attributed to missed tumours, an incomplete resection, re‐implantation of tumour cells after resection, and de novo tumour formation . Current guidelines outline the importance of including muscularis propria of the bladder in every resection .…”
Section: Introductionmentioning
confidence: 99%
“…WLC and TURBT have well-recognized shortcomings including missed tumors, incomplete resection, and understaging (5). Increasingly, adjunctive optical imaging technologies are utilized to augment WLC (6). Photodynamic diagnosis (PDD), based on intravesical administration of the photosensitizer hexaminolevulinate (HAL) coupled with blue light cystoscopy, improves bladder cancer detection and is increasingly clinically utilized (7).…”
Section: Introductionmentioning
confidence: 99%
“…We and other groups have shown that the signal obtained from the tumor is greater and is retained for a longer time for macromolecular probes compared with that of low MW fluorescent molecules 22 , 31 , 32 . The general concept of an activated Turn-ON polymeric or macromolecular probe generating a fluorescence signal was previously proposed 33 ; however, there have been many unique reports on different systems 34 , 35 , mechanisms of activation and/or versatile applications 36 - 38 . Several quantum dots have also shown benefits in the fluorescence image-guided surgery arena, including bladder cancer resection 35 , small MW integrin-targeted RGD probes for colorectal cancer and ureters 39 and fluorescently-tagged targeted antibodies for head-and-neck cancer 34 .…”
Section: Introductionmentioning
confidence: 99%